MODERN POWER SOURCES: ON THE WAY TO ENVIRONMENTAL SAFETY - Пилипчук, Андрій; Чурсанова, Марина (SWorldJournal, 2023)
The article presents a review of modern autonomous power sources. It is difficult to overestimate the role of batteries and accumulators in our era. They have become the basis for many innovations and products, such as smartphones and other electronic de